Stitz-Zeager_College_Algebra_e-book

# 19 we will discuss how we arrived at this

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ow we can use P (k ) in this case to prove P (k + 1), we note that the sum in P (k + 1) is the sum of the ﬁrst k + 1 terms of the sequence ak = a + (k − 1)d for k ≥ 1 while the sum in P (k ) is the sum of the ﬁrst k terms. We compare both side of the equation in P (k + 1). k+1 (a + (j − 1)d) ? k+1 (2a + (k + 1 − 1)d) 2 ? k+1 (2a + kd) 2 = j =1 summing the ﬁrst k + 1 terms k (a + (j − 1)d) + (a + (k + 1 − 1)d) = j =1 summing the ﬁrst k terms adding the (k + 1)st term k ? (2a + (k − 1)d) +(a + kd) = 2 (k + 1)(2a + kd) 2 Using P (k) k (2a + (k − 1)d) + 2(a + kd) 2 = 2ka + k 2 d + 2a + kd 2 2ka + 2a + k 2 d + kd 2 = 2ka + 2a + k 2 d + kd 2 ? Since all of our steps on both sides of the string of equations are reversible, we conclude that the two sides of the equation are equivalent and hence, P (k + 1) is true. By the Principle of Mathematical Induction, we have that P (n) is true for all natural numbers n. 2. We let P (n) be the formula (z )n = z n . The base case P (1) is (z )1 = z 1 , which reduces to z = z which is true. We now assume P (k ) is true, that is, we assume (z )k = z k and attempt to show tha...
View Full Document

## This note was uploaded on 05/03/2013 for the course MATH Algebra taught by Professor Wong during the Fall '13 term at Chicago Academy High School.

Ask a homework question - tutors are online